2021
DOI: 10.35845/kmuj.2021.21653
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tooth Clearing Technique to Determine Root and Canal Morphology of Permanent Mandibular Third Molars in Population of Peshawar: An in Vitro Cross-Sectional Study

Abstract: OBJECTIVE: To find out number of roots, root-canals and canal configuration in permanent mandibular third molars through tooth clearing technique. METHODS: In this cross-sectional study, 193 extracted human mandibular permanent third molars with completely formed apical foramen and intact roots were collected from both genders treated at dental hospitals in Peshawar, Pakistan from 1st July to 31st December 2019. After collection teeth were visually inspected to count number of roots, followed by access c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Most previous studies analyzed AST, ALT and GGT levels in diabetic subjects, and only some investigations included ALP [7,11,17,26]. The increased level of ALP in diabetic individuals in our study is in agreement with the earlier investigations in which ALP increased in diabetic people [11,45,46]. The Tehran Lipid and Glucose Study reported that increasing levels of GGT, ALP and ALT showed a positive association with diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…Most previous studies analyzed AST, ALT and GGT levels in diabetic subjects, and only some investigations included ALP [7,11,17,26]. The increased level of ALP in diabetic individuals in our study is in agreement with the earlier investigations in which ALP increased in diabetic people [11,45,46]. The Tehran Lipid and Glucose Study reported that increasing levels of GGT, ALP and ALT showed a positive association with diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…In the time of the Aryans, the plants of Soma and Homa would be gathered to the light of the moon and would be used by the people, or there are other similar tapas. (Khattak, 1989) [4] . Studying the world literature history always draws our attention to the fact that literature is strong and has a fundamental connection with society.…”
Section: ‫راخېژه‬ ‫وهه‬ ‫سر‬ ‫سپوږميه‬ ‫رېبينه‬ ‫ګوتې‬ ‫کوي‬ ‫لو‬ ‫ګل...mentioning
confidence: 99%